Structural and functional characterization of SARS coronavirus envelope protein E. - Parthasarathy Krupakar. (2011)
The Coronavirus (CoV) that is responsible for the severe acute respiratory syndrome (SARS) contains a small envelope protein, E, which is involved in virus morphogenesis and possibly host apoptosis. Herein we have studied the structure and possible function of the SARS E protein. Our work showed that SARS-CoV E protein TM domain exist as pentamer as determined by PFO-PAGE, SE-AUC analysis, SSID and NMR. We expressed and purified, for the first time, the full length envelope protein from SARS and IBV E using a novel BBP fusion protein. From AUC analysis it was found that SARS and IBV E proteins form pentamers stabilized by TM domain. IR analysis indicates that most part is embedded in hydrated lipid bilayers forming N-terminal alpha helix, an anti-parallel beta sheet and C-terminal random coil regions. SARS-CoV E protein in HEK-293 cells showed sodium ions conductance indicating that it can act as ion channels.